Business Strategy Developmentwith 360° Business Model Innovation Perspective in PT NEC Indonesia - Rachayu, Widhi; Hartoyo; Hannan, Sufrin (School of Business, IPB University (SB-IPB), 2023)
As a company engaged in information technology and telecommunications, PT NEC Indonesia is aware of the opportunities and challenges in the next few years where rapid change, growing complexity and uncertainty are the basis for how the company designs solutions to help customers and society. This study aims to determine the business model applied by PT. NEC Indonesia and to find out the preparation of a business development strategy plan at PT. NEC Indonesia is based on a 360º innovation business model framework with 5 main components, namely value creation, value proposition, value delivery, value capture and value communication. The data obtained are the results of questionnaires and interviews with seven respondents who are company management and several customers. The results showed that the total score of the IFE matrix was 1,93 and the EFE matrix score was 1.68. These results place PT NEC Indonesia in quadrant I, namely high market growth and a strong competitive position. From the analysis of PT NEC Indonesia's business model, it is necessary to make improvements to several components of the 360º BMI framework. The value creation component, the importance of value-added focus on every solution offered by improving services to be more dynamic not only as a customer but more towards being a partner through a co-creation business strategy. While improvements to the value proposition and value capture component with a focus on added value, the initiation of determining the pricing model with value-based-pricing and recurring revenue model can be applied as a diversification in profitability and efficiency. Keywords: co-creation, 360º business model innovation inovasi, reccuring revenue model, swot, value-based-pricing